On the 90th anniversary of the birth of Ludvik Olas - Koltai, Tomaž (Journal for Geography, 2020)
In the current year we note the 90th anniversary of the birth of geographer and profesor Ludvik Olas. In the article is presented his professional career, bibliography and significance of his life work in the development of geography of Slovenia, geography of northeastern Slovenia as well as his importance in the development od Department of Geography in Maribor. His profesional career and bibliography are presented with the analysis of different biographies and his bibliography. The significance of his work was determined with the combination of both.
Keywords: biography; geography; Ludvik Olas; Department of Geography; Prekmurje